Transforming sugarcane bagasse into zeolitic material: a sustainable approach to wastewater treatment - A A, Nuhu; ZN, Garba; Ibrahim, H; Abdulrazak, s (International Journal of Advanced Chemistry, 2024)
Sugarcane bagasse, an abundant agricultural byproduct rich in silicates and cellulose, continues to be underutilized, making a significant contribution to the ever-growing global solid waste predicament. This study delves into the intricate process of producing and enhancing zeolite material derived from economically viable sugarcane bagasse by employing hydrothermal treatment. It meticulously explores four pivotal process variables: particle size (90-200 µm), reagent (0.5 M NaOH+1.5 M NaCl) ratio (0.5-1), contact time (40-72 hr), and temperature (70-100oC), by utilizing 24 full factorial design to optimize synthesis conditions. The investigation carefully delineates the nuanced impacts of these variables on the resulting zeolite porosity. After 16 experimental runs, the study identified the optimal synthesis conditions as follows: a particle size of 90 µm, a reagent ratio of 1, a contact time of 72 hr, and a temperature of 100oC. The fit statistics that signified the adequacy and significance of the developed model are R² = 0.9965, Adjusted R² = 0.9827, Predicted R² = 0.9018; Adeq Precision = 26.6195; Std. Dev. = 1.69 and C.V = 2.72%. Furthermore, the synthesized zeolite exhibited potentially a heightened adsorption capability due to its amplified porosity. This opens up promising avenues for wastewater treatment, offering effective solutions to a myriad of environmental concerns. This approach not only addresses the pressing issue of waste management but also underscores the potential of transforming waste into valuable resources for sustainable development.